Stable isotopes reveal an invasive plant contributes more than native sources to anuran larvae diets. Issue 1 (1st January 2017) - Radanovic, Milica; Milanovich, Joseph R.; Barrett, Kyle; Crawford, John A.
ABSTRACT: Foraging theory suggests organisms increase their fitness through dietary and energetic choices. In nature, organisms choose to consume balanced optimal diets but as exotic plants invade ecosystems, new foraging options become available. Often these plants have different traits and can negatively affect fitness of foragers by lowering survival or growth due to toxicity. Wetland habitats are highly susceptible to plant invasions which can have negative effects on nutrient cycling. The purpose of this study was to examine whether invasion of purple loosestrife ( Lythrum salicaria ) alters tadpole foraging preference thus potentially impacting their survivorship and fitness. We designed a common garden experiment and utilized stable isotopic signatures to investigate the contribution of purple loosestrife and native hardwood detritus to larval wood frog ( Rana sylvatica ) and southern leopard frog ( Rana sphenocephala ) diets. Tadpoles derived a higher percentage of resources from purple loosestrife compared to native hardwood detritus when presented with both options, despite its high concentration of toxic secondary compounds. It is unknown if tadpoles can detect competing fitness signals that may be associated with higher nutrient and toxicity levels in purple loosestrife. Discovering the presence or absence of such signals will promote a greater understanding of selective foraging in changing environments.